2021
DOI: 10.3389/fonc.2021.633579
|View full text |Cite
|
Sign up to set email alerts
|

Control Analysis of Protein-Protein Interaction Network Reveals Potential Regulatory Targets for MYCN

Abstract: BackgroundMYCN is an oncogenic transcription factor of the MYC family and plays an important role in the formation of tissues and organs during development before birth. Due to the difficulty in drugging MYCN directly, revealing the molecules in MYCN regulatory networks will help to identify effective therapeutic targets.MethodsWe utilized network controllability theory, a recent developed powerful tool, to identify the potential drug target around MYCN based on Protein-Protein interaction network of MYCN. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…However, MYCN itself has a short half-life and complex protein structure, so it is difficult to directly target. Fortunately, we can identify the molecules that directly interact with MYCN by monitoring the MYCN network and applying control signals to achieve indirect regulation, which is expected to improve the disease state [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, MYCN itself has a short half-life and complex protein structure, so it is difficult to directly target. Fortunately, we can identify the molecules that directly interact with MYCN by monitoring the MYCN network and applying control signals to achieve indirect regulation, which is expected to improve the disease state [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recent works have shown that minimum driver nodes (controllers) are not only important to control the network but also that they have been associated to important biological functions 3 7 . In particular, network controllability has been applied to identify cancer-related genes 3 , 8 12 , drug-targets 8 , 13 , disease-related non-coding RNAs (ncRNAs) 14 , virus-targeted proteins 3 , 15 , 16 and has also been used to predict specific neuron functions 17 as well as to unveil the human brain functional structure 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental goal of network controllability is to drive the network from any initial state to a desired target state via specific input nodes [19]. Currently, network control theory has been applied in various biological networks, such as protein interaction networks [20], virus-protein networks [21], cancer regulatory networks [22], and brain networks [18]. In various network controllability methods, average controllability is considered a significant approach in the context of mental disorders.…”
Section: Introductionmentioning
confidence: 99%